Asialoglycoprotein receptor-targeted perfluorooctylbromide as a targeted contrast agent for evaluating the severity of carbon tetrachloride-induced acute liver damage in rats - Yu, Jinhong; Yang, Chaofeng; Zhang, Pengwei; Wei, Min; Li, Yang (Frontiers in Chemistry, 2025)
Asialoglycoprotein receptor (ASGPR) is an endocytic C-type lectin receptor in hepatocytes. Acute and chronic liver diseases can result in the decreased expression and content of this receptor. The objective of this study was to determine whether ASGPR-targeted perfluorooctylbromide (PFOB) can enhance ultrasound imaging signals and evaluate the severity of carbon tetrachloride (CCl4)-induced acute liver damage in rats. The specificity of ASGPR-targeted PFOB for hepatocytes L-02 was investigated in vitro. In vivo, all rats were treated with either ASGPR-targeted PFOB or PFOB, and ultrasound imaging of the livers was performed to evaluate the effect of these treatments on the imaging signal. The effects of CCl4 injection were also examined by measuring the percentage of apoptotic hepatocytes and ASGPR content. We first confirmed that ASGPR-targeted PFOB can be targeted specifically to hepatocytes L-02. In the healthy rat group, ASGPR-targeted PFOB increased the echo intensity (EI) of the liver by 87.47 dB, which was significantly higher than the EI increase observed with PFOB treatment (37.38 dB; P < 0.001), and the mean elimination times of the contrast agents were 282 ± 13.17 min and 225 ± 10.80 min for the ASGPR-targeted PFOB and PFOB groups, respectively (P < 0.001). In the CCl4-induced acute liver injury group, significant differences were observed in each group before and after administration of ASGPR-targeted PFOB. Significant differences were also observed between the different groups. The degree of reduction in peak EI correlated with the total dose of the CCl4. A decline in ASGPR content was correlated with the severity of acute liver damage using the CCl4-induced model. These findings suggest that ASGPR-targeted PFOB enhances ultrasound imaging and is a reliable tool for assessing the severity of acute liver damage in rats.